Temporal Variation of Black Carbon Aerosol Concentration during Monsoon in Kathmandu Valley - Sharma, Ram K.; Bhattarai, Binod K; Sapkota, Balkrishna; Gewali, Mohan Bahadur; Kjeldstad, Berit (Journal of the Institute of Engineering, 2014)
Black carbon aerosol was measured continuously for three months June, July and August 2009 at G block of Pulchowk Campus, Institute of Engineering, Department of Engineering Science and Humanities using Magee Scientific Aethalometer AE 31 model. The study period corresponds to monsoon season over Nepal. The study site Pulchow Campus is located at 27°22’N latitude and 85°32’E longitude. The diurnal variation of aerosol black carbon shows two peaks during morning and late evening. These two distinct peaks occur due to gradual increase in the anthropogenic activities and rush hour traffic. Among the three months of monsoon highest monthly average was observed during June while lowest during July and moderate on August with 5.3 7mu&g/m3, 3.0 μg/m3 and 3.8 μg/m3 respectively. The average rain fall in these months were 126mm, 326.3mm and 383mm respectively. The concentration of aerosol black carbon is higher in dry month than rainy months because it is washed by rain once it is released in the atmosphere. In the daily average the highest value of aerosol black carbon was observed on 9th June as 8.2 μg/m3 while lowest value on 16th August as low as 1.9μg/m3. DOI: http://dx.doi.org/10.3126/jie.v9i1.10666 Journal of the Institute of Engineering, Vol. 9, No. 1, pp. 27–35